Fetal haematology in rhesus isoimmunisation. Issue 6469 (2nd March 1985) - Nicolaides, K H; Rodeck, C H; Millar, D S; Mibashan, R S
Abstract : Haematological studies were carried out in pure fetal blood samples obtained fetoscopically in 29 rhesus isoimmunised pregnancies at 18-24 weeks' gestation, and the values were compared with those obtained in 62 normal control pregnancies. Fetal reticulocytosis or erythroblastaemia was seen only in association with a haemoglobin concentration of 4 g/dl or less. Ten of the 14 fetuses with a haemoglobin concentration below 4 g/dl showed ultrasonographic evidence of hydrops.